English Classroom:Ideals and Realities Converting English Classroom into Activity Laboratory - Bharadwaj, Apoorva (Journal of Engineering Education Transformations, 2005)
The word laboratory might sound odd when we use it with the expression 'English classroom', though we are conversant with the concept of language laboratory. The notion of laboratory which is being discussed here has nothing to do with any kind of physical infrastructure but with the spirit of experimentation. The classroom can be used as a platform for conducting experiments with the usage of language coupled with presentation techniques. Thus here instead of technology we use technique.